Про про профессии - Борисова Наталья (Другой, другие, о других. Детский проект Людмилы Улицкой, 2012)
Экземпляры: ДБ (20141015) / Инвентарный номер: 43644 / Цена: / Сис.шифр: 84Р7 / Авт.знак: Б 82 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6